Interleukin-1β affects the phospholipid biosynthesis of fibroblast-like synoviocytes from human osteoarthritic knee joints. Issue 11 (November 2017) - Sluzalska, K.D.; Liebisch, G.; Lochnit, G.; Ishaque, B.; Hackstein, H.; Schmitz, G.; Rickert, M.; Steinmeyer, J.
Summary: Objective: Phospholipids (PLs), together with hyaluronan and lubricin, are involved in boundary lubrication within human articular joints. Levels of lubricants in synovial fluid (SF) have been found to be associated with the health status of the joint. However, the biosynthesis and release of PLs within human joints remains poorly understood. This study contributes to our understanding of the effects of cytokines on the biosynthesis of PLs using cultured fibroblast-like synoviocytes (FLS) from human osteoarthritic knee joints. Methods: Cultured FLS were stimulated with IL-1β, TNFα, IL-6, or inhibitors of cell signaling pathways such as QNZ, SB203580 and SP600125 in the presence of stable isotope-labeled precursors of PLs. Lipids were extracted and quantified using electrospray ionization tandem mass spectrometry (ESI-MS/MS). Results: Our analyses provide for the first time a detailed overview of PL species being synthesized by FLS. IL-1β increased the biosynthesis of both phosphatidylethanolamine (PE) and PE-based plasmalogens. We show here that the NF-κB, p38 MAPK and JNK signaling pathways are all involved in IL-1β-induced PL biosynthesis. IL-6 had no impact on PLs, whereas TNFα increased the biosynthesis of all PL classes. Conclusion: The biosynthesis of various PLs is controlled by IL-1β and TNFα. Our detailed PL species analysis revealed that FLS can partly contribute to the elevated PL levels found in human osteoarthritis (OA) SF. IL-1β in particular stimulates PE and PE-based plasmalogens which can act as cell-protective antioxidants. These results suggest that during OA progression, FLS undergo alterations in their PL composition to adapt to the new diseased environment.